La familia de Santo Toribio Alfonso de Mogrovejo (siglos XIV-XVII) - Torres, Margarita (Estudios humanísticos. Historia, 2009)
With this anide we try to update a previous work about Santo Toribio de Mogrovejo's family and ancestors. The main point is focused on Maestre de Campo Francisco de Quiñones, his brother-in-law, who was governor of Chile and General. His descendants were divided in two different lines:Indian and Spanish ones. We study this familiar environment, common in Spanish nobility in XVII century.